5(2x-9)+7x=

Simple and best practice solution for 5(2x-9)+7x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-9)+7x= equation:


Simplifying
5(2x + -9) + 7x = 0

Reorder the terms:
5(-9 + 2x) + 7x = 0
(-9 * 5 + 2x * 5) + 7x = 0
(-45 + 10x) + 7x = 0

Combine like terms: 10x + 7x = 17x
-45 + 17x = 0

Solving
-45 + 17x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '45' to each side of the equation.
-45 + 45 + 17x = 0 + 45

Combine like terms: -45 + 45 = 0
0 + 17x = 0 + 45
17x = 0 + 45

Combine like terms: 0 + 45 = 45
17x = 45

Divide each side by '17'.
x = 2.647058824

Simplifying
x = 2.647058824

See similar equations:

| 3p+2p+4y+5y= | | 4x+5=4x-28 | | 31-2x=10-9x | | -(2x-3)-(2x-6)+5=-6(x-1)-(2x-7)+3 | | (3t^2+6t)+(-9t^2-5t+5)= | | x(920-2x)=A(x) | | 3x+10=-26-6x | | 13g=39 | | 25(x-1)=x+1 | | 920x-2x^2=0 | | (-6b^2-2b-1)+(-2b^2+4b)= | | 5(2x-9)+7= | | 5x+4(5x+3)= | | 12(y)=384 | | 1996+43x+7385-67x= | | -18n*18=9 | | 12x-13-6x+4= | | 9p-7=74 | | 18n*18=9 | | 4+42x=21x+16 | | 3k-11=5-k | | p=7k^2-14k+1 | | 18.7+k=32.2 | | -18nx=9 | | (-n^3-8n-6)+(-8n^3+9n)= | | 3x-7+5=-(4x+7)+17x | | 0.5r+3=6 | | 9x+2y=114 | | 0.5+3=6 | | c=4d+5 | | 4(a-11)-7(2a+1)=-2.28 | | Z+6.8=15 |

Equations solver categories